2018
DOI: 10.1080/00981389.2018.1508113
|View full text |Cite
|
Sign up to set email alerts
|

Physical and psychosocial factors associated with depression among adults with type 2 diabetes mellitus at a Federally Qualified Healthcare Center

Abstract: The findings support that health care providers developing care plans for individuals with diabetes need to include assessments and interventions that address both the physical and psychosocial needs of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
1
2
0
1
Order By: Relevance
“…Furthermore, the authors further buttressed the observation that the significant effects of poverty and education attainment on glycosylated hemoglobin levels were mediated by avoidance coping and by depressive symptoms [40]. Additionally, taking medication for a long time and receiving insulin as treatment increased the odds of having depression, as reported in previous studies [36,41] -similar findings have been reported elsewhere [42][43][44].…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, the authors further buttressed the observation that the significant effects of poverty and education attainment on glycosylated hemoglobin levels were mediated by avoidance coping and by depressive symptoms [40]. Additionally, taking medication for a long time and receiving insulin as treatment increased the odds of having depression, as reported in previous studies [36,41] -similar findings have been reported elsewhere [42][43][44].…”
Section: Discussionsupporting
confidence: 72%
“…Stressful events could provoke and cause relapses of depression in both the general and diabetic population. Lee, Brazeal, Choiet al 15 studied 421 patients with type 2 diabetes mellitus and revealed that the patients with stressful events had higher prevalence of depression than those who had no stressful events. Bădescu, Tătaru, Kobylinskaet al 16 also demonstrated similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Os artigos mostraram uma caracterização de pessoas convivendo com diabetes com faixa etária variada de 18 a 80 anos, onde (1) estudo foi com pacientes diabéticos do tipo 1 e 2 8 , (7) pacientes diabéticos do tipo (2) 4-5-8-9-10-11-12 e (1) pacientes diabéticos do tipo 1 7 . Os locais nos quais ocorreram as pesquisas foram: Clinicas médicas (2) [9][10][11][12][13] , Hospitais (2) [8][9][10][11] , Centros de Saúde (2) [10][11][12] , de forma online em domicílio (1) 14 , Unidades de Saúde (1) 5 e ambulatórios (1) 4 .…”
Section: Resultsunclassified